Radio propagation modelling in the downlink LTE - Deroussent, Andrew; Sandrasegaran, Kumbesan; Mohd. Ramli, Huda Adibah; Basukala, Riyaj (2010)
In order to support development of third generation partnership project long term evolution (3GPP LTE) packet scheduling algorithms, research has been conducted into several radio propagation effects. The radio channels of interest are the downlink (eNodeB to user equipment) of LTE mobile networks. Through network simulator modification and repeated testing the effects of error and delay in reporting available user mobile Signal to Noise Ratio (SNR) has been investigated. Simulation results show that errors in reported SNR will increase erroneous transmission, and the effect increased with greater numbers of users. Simulations results also show that the effect of processing delay is largely dependent on the velocity of the affected mobile user.